Symbiotic germination and development of myco-heterotrophic plants in nature ontogeny of Corallorhiza trifida and characterization of its mycorrhizal fungi - McKENDRICK, S L (The New phytologist, 2000)
The processes of symbiotic germination and seedling development were analysed in the myco-heterotrophic orchid Corallorhiza trifida, seeds of which were buried in 'packets' either adjacent to or at varying distances from adult plants in defined communities of ectomycorrhizal tree species. Germination occurred within eight months of burial under Betula-Alnus and within seven months under Salix repens. It was always associated with penetration of the suspensor by a clamp-forming mycorrhizal fungus. Four distinct developmental stages were defined and the rates of transition through these stages were plotted. There was no evidence of a relationship between extent of germination or rate of development and the presence of naturally distributed plants of C. trifida at the spatial scale of 1 m. The best germination and the most rapid rate of development of C. trifida seedlings occurred in a Salix repens community located at a considerable distance from any extant C. trifida population. Determination of internal transcribed spacer (ITS) RFLPs and of gene sequences of the fungi involved in symbiotic germination and growth of C. trifida, revealed them to belong exclusively to the Thelephora-Tomentella complex of the Thelephoraceae. These fungi are known also to be ectomycorrhizal associates of trees. It is hypothesized that the rate of growth of the C. trifida seedlings is determined by the ability of the fungal symbionts to transfer carbon from their ectomycorrhizal co-associates